Role Of Endoscopic Ultrasound In Diagnosis Of Esophageal Varices (Journal of Pharmaceutical Negative Results, 2023)
Background: Bleeding esophageal varices constitute a digestive emergency with poor treatment response, numerous complications, and a high death rate. Moreover, bleeding for the first time is one of the most serious complications in cirrhotic patients .To decrease the death rate, predicting the occurrence of bleeding esophageal and gastric varices have been extensively explored. Previous research has shown that PHT can cause the occurrence of collateral and perforator veins, as well as varicose veins in the esophagus. After endoscopic treatment, patients with collateral and perforator veins are more likely to experience the recurrence of varicose veins. Transabdominal ultrasound (US), computed tomography (CT), and magnetic resonance imaging (MRI) are established diagnostic tools for abdominal diseases. Despite their widespread use, these techniques have limitations. In contrast, EUS complements these modalities, and has been proven useful for evaluating the mediastinum, pancreas, biliary tract, gastrointestinal tract, liver, and adrenal glands. EUS enables observation near esophageal varices and helps to understand the localized detailed hemodynamics of esophageal varices, this suggests that useful information can be obtained for the selection of treatment suited to the hemodynamics of each individual varix and for the prediction of recurrence. Furthermore, EUS is considered highly useful for determining the treatment response and can easily evaluate the presence or absence of residual blood flow that is difficult to determine by normal endoscopic observation. Over the past two decades,(EUS) has undergone a transition from being a novel imaging technique to a clinical diagnostic test that is necessary for the optimal management of gastrointestinal diseases. Along with established clinical indications, such as gastrointestinal and pancreatic tumor staging, differential diagnosis of submucosal lesions, evaluation of solid and cystic pancreatic masses, detection of lymph nodes and fine needle aspiration (FNA), new applications have been suggested such as a clinical role for EUS in PHT